Association between cognitive function and performance on effort based decision making in patients with major depressive disorder treated with Vortioxetine - Subramaniapillai, Mehala; Mansur, Rodrigo B.; Zuckerman, Hannah; Park, Caroline; Lee, Yena; Iacobucci, Michelle; Cao, Bing; Ho, Roger; Lin, Kangguang; Phan, Lee; McIntyre, Roger S. (Comprehensive psychiatry, 2019)
It is well established that deficits in motivation, reward, and cognition are common during and in between syndromal episodes of depression as part of Major Depressive Disorder (MDD). Informed by evidence indicating functional and structural interconnectivity between cognitive and reward brain circuits, we preliminarily evaluate the association between measures of cognitive performance and reward/motivation. This is a post-hoc analysis of a primary study (i.e. the THINC-it sensitivity to change study). Adults (18–65 years of age) meeting DSM-5 criteria for MDD, single-episode or recurrent confirmed by M.I.N.I. with moderate severity or greater (i.e. Montgomery Asberg Depression Rating Scale ≥20). All eligible subjects received vortioxetine 10–20 mg open-label for 8 weeks. The Effort Expenditure Reward Task (EEfRT) was the principal measure of motivation and reward. We directly compare the effects of cognitive measures and depressive symptoms on effort-based decision-making using the THINC-it composite score and MADRS total score. Twenty-one participants with MDD (Mean age = 38.47, SD = 12.85) and 20 healthy volunteers (Mean age = 41.50, SD = 14.21) completed the optional EEfRT task. Amongst individuals with MDD, performance in processing speed, executive function (i.e. Trails B) and overall composite cognitive score was positively associated with the proportion of hard-task choices in the high reward condition (i.e. greater reward valuation). Across both groups, a greater probability (χ2 = 1.137) and magnitude of reward (χ2 = 0.045) was associated with increased effort (i.e. choosing the hard task more frequently). Using fully factored GEE models, we observed a positive association between performance on the Trails test (β = 2.223, SE = 0.928, p = 0.017) as well as the composite score (β = 0.978, SE = 0.0.459, p = 0.033), and greater effort for high rewards. In addition, it was observed that a positive association (i.e. greater effort for reward in higher probability) was observed with depressive symptoms and overall cognitive measures. Herein, we observed that an association exists between overall cognitive function, notably processing speed and executive function and reward function. Specifically, a greater effort for hard task rewards (using the EEfRT task) was manifested in individuals exhibiting higher levels of cognitive performance in a well-characterized sample of MDD treated with Vortioxetine. •Cognitive function highly correlates with measures of reward and motivation in adults with major depressive disorder (MDD)•Processing speed, executive function and overall cognition was positively associated with greater reward valuation•Overall cognition positively correlated (i.e. greater effort for reward in higher probability) with depressive symptoms•Self-reported measures of anhedonia and reward valuation are distinct domains of psychopathology in those with MDD